Household Income and expenditure behavior in Northern province in Sri Lanka: A non-parametric analysis . - Koperunthevy, K.; Paulina Mary, G.P.; Neruja, N. (Vavuniya Campus of the University of Jaffna., 2020)
The study aims to identify households' income and expenditure behavior based on selected theories in Sri Lanka. The sample was selected from households in five districts in the Northern province such as Jaffna, Mannar, Mullaitivu, Kilinochchi and Vavuniya. By using a systematic sampling method, 930 households were identified and a self-administrated questionnaire was issued to collect data. Finally, 909 usable questionnaires were considered, and then data were analysed with a non-parametric analysis. The results reveal that majority (79.7%) of the household income is less than Rs.100,000 and 62.6% of the income used for consumption purposes. The majority of the respondents accepted that their consumption behaviour was changed during the post war era. According to the chi-square test, the relative income hypothesis was rejected and the permanent income hypothesis was accepted. Simultaneously, the application of the hyperbolic discounting model is more suitable for low- and middle-income people. Therefore, the study concludes that households' expenditure behavior in Sri Lankan is connected with their level of income.
Keywords: : Hyperbolic discountingg; Income and expenditure; Permanent income; Relative income